Outcome after Interlocking intramedullary nailing of humeral shaft fractures - Ashwani Ummat; Sonia Kochhar; Kunal Bansal; Rahul Bhardwaj; Chetan Sharma (International Journal of Medical Research and Review, 2016)
Introduction: Management of fractures of humeral shaft is always a challenging problem to deal with as they are very frequently associated with multiple injuries, leading to complications. Interlocking intramedullary nails have gained popularity now a days for stabilization of humeral shaft fractures due to load sharing nature of implant, preservation of fracture haematoma, minimal exposure and rigid fixation with early mobilization.Material & Methods: A prospective clinical study on fifty patients of humeral shaft fractures was performed using antegrade locked intramedullary nailing in our hospital setting to evaluate the incidence of complications associated with this method of humeral shaft fracture fixation.Results: Superficial wound infection occurred in four cases (8%). Shortening of one cm was observed in one case (2%) and troublesome shoulder pain remained in two patients (4%). Persistent restriction of shoulder movements remained in twelve patients (24%) at 6 months, non-union occurred in two patients (4%), iatrogenic transient radial nerve palsy occurred in four patients (8%). Two patients (8%) developed myositis ossificans of shoulder joint and two patient (8%) developed hypertrophy of scar.Conclusion: A number of technical errors and complications, which we consider technique specific, were registered. The analysis and avoidance of these complications, related to intramedullary nailing of the humerus, will allow intramedullary nails to successfully bridge the gap between bracing and plating.